Insights From Invasive Cardiopulmonary Exercise Testing of Patients With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Joseph, Phillip; Arevalo, Carlo; Oliveira, Rudolf K F; Faria-Urbina, Mariana; Felsenstein, Donna; Oaklander, Anne Louise; Systrom, David M (Chest, 2021)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) affects tens of millions worldwide; the causes of exertional intolerance are poorly understood. The ME/CFS label overlaps with postural orthostatic tachycardia (POTS) and fibromyalgia, and objective evidence of small fiber neuropathy (SFN) is reported in approximately 50% of POTS and fibromyalgia patients. Can invasive cardiopulmonary exercise testing (iCPET) and PGP9.5-immunolabeled lower-leg skin biopsies inform the pathophysiology of ME/CFS exertional intolerance and potential relationships with SFN? We analyzed 1,516 upright invasive iCPETs performed to investigate exertional intolerance. After excluding patients with intrinsic heart or lung disease and selecting those with right atrial pressures (RAP) <6.5 mm Hg, results from 160 patients meeting ME/CFS criteria who had skin biopsy test results were compared with 36 control subjects. Rest-to-peak changes in cardiac output (Qc) were compared with oxygen uptake (Qc/VO slope) to identify participants with low, normal, or high pulmonary blood flow by Qc/VO tertiles. During exercise, the 160 ME/CFS patients averaged lower RAP (1.9 ± 2 vs 8.3 ± 1.5; P < .0001) and peak VO (80% ± 21% vs 101.4% ± 17%; P < .0001) than control subjects. The low-flow tertile had lower peak Qc than the normal and high-flow tertiles (88.4% ± 19% vs 99.5% ± 23.8% vs 99.9% ± 19.5% predicted; P < .01). In contrast, systemic oxygen extraction was impaired in high-flow vs low- and normal-flow participants (0.74% ± 0.1% vs 0.88 ± 0.11 vs 0.86 ± 0.1; P < .0001) in association with peripheral left-to-right shunting. Among the 160 ME/CFS patient biopsies, 31% were consistent with SFN (epidermal innervation ≤5.0% of predicted; P < .0001). Denervation severity did not correlate with exertional measures. These results identify two types of peripheral neurovascular dysregulation that are biologically plausible contributors to ME/CFS exertional intolerance-depressed Qc from impaired venous return, and impaired peripheral oxygen extraction. In patients with small-fiber pathology, neuropathic dysregulation causing microvascular dilation may limit exertion by shunting oxygenated blood from capillary beds and reducing cardiac return.